Factors Influencing Nurses’ Resistance to Change: A Systematic Review - Alsufyani, Abdulaziz M.; Althobaiti, Fahad M.; Aljuaid, Sayer (Nurse Media Journal of Nursing, 2026)
Background: The effectiveness of change initiatives in healthcare systems is often undermined by nurses’ resistance to change, resulting in unfavorable outcomes. Despite nurses’ central role in hospital-based initiatives, multiple factors may contribute to this resistance. The existing literature remains insufficient in synthesizing comprehensive, integrative evidence on this issue. This gap highlights the need for a systematic review to inform tailored interventions that enhance the implementation and sustainability of change in healthcare.Purpose: This review provides a comprehensive overview of the factors influencing resistance to change in the nursing profession.Methods: Following the PRISMA guidelines, a systematic search was conducted in PubMed, CINAHL, Scopus, and Web of Science using terms related to “resistance to change” and “nursing.” Studies examining resistance factors among nurses, published in English between 2010 and 2024, were included. Two independent reviewers conducted data extraction and quality assessment using the Mixed-Methods Appraisal Tool. Content and thematic analyses were performed to generate a comprehensive synthesis.Results: Of the 646 records identified, 14 studies met the inclusion criteria and were included in the final review. The findings revealed significant individual, interpersonal, and organizational factors contributing to nurses’ resistance to change. Individual-level factors included low readiness for change, limited empowerment, and personality characteristics. Interpersonal factors were associated with poor communication, limited stakeholder engagement, and weak leader–member relationships. At the organizational level, the factors included ineffective leadership styles, inadequate training, and dysfunctional organizational culture.Conclusion: Resistance to change among nurses is multifaceted and context-dependent. These findings underscore the need for targeted interventions, particularly emphasizing the importance of effective communication, training, and nurse involvement in enhancing the sustainability of change initiatives in healthcare settings.